Pengaruh Strategi Harga Dan Promosi Terhadap Minat Beli Konsumen Pada Produk Frozen Food (Studi Pada Akun Tiktok @Dakonfrozenfood) - Nurhalima Nurhalima; Megawati Megawati; Akmal Abdullah (Jurnal Manajemen Bisnis Digital Terkini, 2024)
Nowadays, many people choose to eat instant or fast food including frozen food. Dakon Frozen Food is one of the The most complete Frozen Food shop in the Sleman area, Yogyakarta Province. Objective This study is to determine the effect of price and promotion strategies on consumer buying interest in frozen food products offered by Dakon Frozen Food. on consumer buying interest in frozen food products offered by Dakon Frozen Food. by Dakon Frozen Food. The type of data used in this study is quantitative data obtained from distributing questionnaires with 30 respondents. respondents, analyzed using multiple linear regression analysis with the help of SPSS version 23. The research process was carried out with the stages of observation, distributing questionnaires, and literature study. questionnaires, and literature studies. Instrument trials using validity and reliability tests. reliability test. The data analysis methods used are classical assumption tests, multiple linear regression tests, partial (t) tests, and multiple linear regression tests. multiple linear regression test, partial test (t), simultaneous test (F), and determination coefficient test. determination. The results showed that partially price does not significant effect on buying interest, while promotional strategies has a significant effect on buying interest. As for the simultaneous price and promotional strategies have a significant effect on buying interest.